2017
DOI: 10.1124/mol.116.107698
|View full text |Cite
|
Sign up to set email alerts
|

GRK2 Mediates Arginine Vasopressin-Induced Interleukin-6 Production via Nuclear Factor-κB Signaling Neonatal Rat Cardiac Fibroblast

Abstract: Interleukin 6 (IL-6), which is elevated in patients with congestive heart failure and acts as both a chronic marker of inflammation and an acute-phase reactant, is associated with myocardial damage. Circulating levels of arginine vasopressin (AVP) are elevated during cardiac stress and could be a factor for cardiac inflammation and fibrosis. Our previous study has shown that AVP promotes the proliferation of neonatal rat cardiac fibroblasts (NRCFs) throughV vasopressin receptor-mediated G protein-coupled recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
(71 reference statements)
0
15
0
Order By: Relevance
“…However, the Food and Drug Administration-approved SSRI paroxetine was identified using a high throughput aptamer displacement assay to bind directly to GRK2 to inhibit its ability to phosphorylate rhodopsin, tubulin and thyrotropin-releasing hormone receptor, while increasing βAR-stimulated cardiomyocyte (in vitro) and cardiac (in vivo) contractility 7 . Subsequently, paroxetine has been shown to reverse cardiac dysfunction induced by either ischemia 8 or high fat diet 18 , inhibit T cell activation 19 and decrease fibroblast cytokine production 20 . Despite the increasing use of paroxetine in studies in which its effects are attributed to inhibition of receptor desensitization processes classically engaged by GRK2, such as βarr recruitment and GPCR internalization, no studies have confirmed whether it actually attenuates these responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Food and Drug Administration-approved SSRI paroxetine was identified using a high throughput aptamer displacement assay to bind directly to GRK2 to inhibit its ability to phosphorylate rhodopsin, tubulin and thyrotropin-releasing hormone receptor, while increasing βAR-stimulated cardiomyocyte (in vitro) and cardiac (in vivo) contractility 7 . Subsequently, paroxetine has been shown to reverse cardiac dysfunction induced by either ischemia 8 or high fat diet 18 , inhibit T cell activation 19 and decrease fibroblast cytokine production 20 . Despite the increasing use of paroxetine in studies in which its effects are attributed to inhibition of receptor desensitization processes classically engaged by GRK2, such as βarr recruitment and GPCR internalization, no studies have confirmed whether it actually attenuates these responses.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that AVP induces IL-6 production via NF-κB signaling in neonatal rat cardiac fibroblasts [ 33 ] and cultured ARCFs (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 95%
“…Other evidence of GRK2 related to DCM was provided by inhibiting the GRK2 expression. Inhibition of GRK2 increased oxygen consumption rates and ATP production, reduced the degree of myocardial remodeling, and abolished the AVP‐induced IL‐6 production and NF‐κB activation . Moreover, a very recent paper showed that GRK2 inhibition can be safely achieved with beneficial effects in diabetes, and beyond its effects on the glycemic profile, exerted the anti‐inflammatory and antioxidative effect on the heart, which indicated a potential therapeutic action on DCM …”
Section: Discussionmentioning
confidence: 95%
“…Inhibition of GRK2 increased oxygen consumption rates and ATP production, 33 reduced the degree of myocardial remodeling, 34 and abolished the AVP-induced IL-6 production and NF-κB activation. 35 Moreover, a very recent paper showed that GRK2 inhibition can be safely achieved with beneficial effects in diabetes, and beyond its effects on the glycemic profile, exerted the anti-inflammatory and antioxidative effect on the heart, which indicated a potential therapeutic action on DCM. 36 In addition to β-adrenergic receptor-mediated signaling, other mechanisms including insulin resistance, fatty acid oxidation, and cardiomyocyte oxidative stress might be involved in the relation between GRK2 and DCM.…”
Section: Discussionmentioning
confidence: 99%